Identifikasi Pendekatan Shallow Water Equation Dalam Simulasi 2D Gelombang Tsunami di Pantai Keburuhan Purworejo - Benny Hartanto; Ningrum Astriawati (Sekolah Tinggi Maritim Yogyakarta, 2020)
Purworejo Regency is one of the five areas affected by the Java tsunami run-up on July 17, 2006. Based on the results of the Rapid Survey by BPDP and BPPT, along Pantai Kebempuan is the location of the tsunami run-up in Purworejo Regency at coordinates 109,912 LS -7.85 East BT 1.7 meters. The purpose of this study is to estimate the tsunami travel time, distribution of tsunami wave heights and tsunami coverage areas due to the impact of the Java earthquake on July 17, 2006 at Pantai Kebempuan, Purworejo. The method used is a descriptive analytical method with a quantitative approach. The data used in this study are the high point, bathymetry, earthquake parameters, tidal forecasts for the waters of the Kebempuan coast, Geo Eye 1 image data, and beach slope. Tsunami modeling using COMCOT v 1.7 software with the Java 17 July 2006. Based on data processing, it is known that the maximum wave speed is 3.8788 m / s. In the 40th minute, the initial amplitude of the tsunami wave of 1,644 meters had reached the Kebshore Beach. The widest tsunami coverage area and the maximum farthest distance to occur on the Labor Beach are 1.23 km2 and 1.4 km. Based on the results of verification with an RSR value of 0.26. The results of validation of tsunami simulations using COMCOT v.17 note that the height of the model tsunami run-up is quite in accordance with the run-up data that occurred at the time of the incident, with an RSR value of 0.29 and a CF of 1.63.